2008
DOI: 10.1371/journal.pone.0001872
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Genes Do Not Influence Response or Tolerance to Citalopram in the STAR*D Sample

Abstract: BackgroundWe sought to determine whether clinical response or tolerance to the Selective Serotonin Reuptake Inhibitor (SSRI) citalopram is associated with genetic polymorphisms in potentially relevant pharmacokinetic enzymes.MethodologyWe used a two-stage case-control study design in which we split the sample of 1,953 subjects from the Sequenced Treatment Alternatives to Relieve Depression (STAR*D) trial into a discovery (n = 831) and validation set (n = 1,046). Fifteen polymorphisms from five (CYP2D6, ABCB1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
111
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(117 citation statements)
references
References 41 publications
3
111
2
1
Order By: Relevance
“…The effect of genetic variation has been studied at the pharmacokinetic (eg, CYP2D6; Kirchheiner and Seeringer, 2007;Peters et al, 2008;Tomalik-Scharte et al, 2008;Uhr et al, 2008), the pharmacodynamic (Binder and Holsboer, 2006;Kato and Serretti 2008;Horstmann and Binder, 2009), and the bioavailability level (eg, ABCB1; Uhr et al, 2008). Up till now all studies were driven by hypothesis, analyzing candidate genes in the main systems currently implicated in the etiology of major depression and mechanism of action of antidepressant drugs (Holsboer, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of genetic variation has been studied at the pharmacokinetic (eg, CYP2D6; Kirchheiner and Seeringer, 2007;Peters et al, 2008;Tomalik-Scharte et al, 2008;Uhr et al, 2008), the pharmacodynamic (Binder and Holsboer, 2006;Kato and Serretti 2008;Horstmann and Binder, 2009), and the bioavailability level (eg, ABCB1; Uhr et al, 2008). Up till now all studies were driven by hypothesis, analyzing candidate genes in the main systems currently implicated in the etiology of major depression and mechanism of action of antidepressant drugs (Holsboer, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Other genes of interest that were previously reported to be significant included FKBP5 (38), PDE11A (39,40), and BDNF (41). Finally, genes with pharmacokinetic function were also assessed in this group and included CYP2D6, CYP2C19, CYP3A4, CYP3A5, and ABCB1 (42). …”
Section: Results Of Pharmacogenetics Studies In Star*dmentioning
confidence: 99%
“…Finally, a tolerance outcome was based on study exit data. All participants who continued with citalopram were considered tolerant, and patients who refused to continue level 1 treatment or who left the study because of side effects were considered intolerant (42). …”
Section: Results Of Pharmacogenetics Studies In Star*dmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacogenetic studies of antidepressants in the STAR*D trial have identified genes associated with treatment response (Hu et al, 2007;Lekman et al, 2008a;McMahon et al, 2006;Paddock, 2008), treatment resistance (Perlis et al, 2008), and treatment-emergent suicidal ideation (Laje et al, 2009;Laje et al, 2007;Perlis et al, 2007). In addition, polymorphisms in genes that encode drug-metabolizing enzymes and transporters have been tested for correlation with treatment response (Peters et al, 2008). Genes that were significantly associated with response to citalopram include FKBP5 (Lekman et al, 2008a), glutamate receptor, ionotropic kainite 1 (GRIK1), N-methyl d-aspartate 2A (GRIN2A), 5-hydrxytryptamine receptor 2A (HTR2A), potassium channel, subfamily K, member 2 (KCNK2), phosphodiesterase (PDE), and solute carrier family 6 member 4 (SLC6A4) (E. Lin & Chen, 2008).…”
Section: Genetic Predictors Of Depression and Antidepressant Responsementioning
confidence: 99%